Políticas y programas de la economía circular en Ecuador 2008-2021. - Morocho Matute, Denisse Andreina; Nagua Capa, Karol Michelle (Machala : Universidad Técnica de Machala, 2024)
The circular economy is presented as an innovative approach that seeks to revolutionize the way we produce, consume and manage resources. The implementation of circular economy policies and programs is essential to achieve sustainable development. This involves adopting preventive practices, encouraging reuse, recycling, promoting eco-design and responsible consumption. Within this framework, the design of products and materials is aimed at maintaining their value and usefulness for as long as possible, through practices such as sustainable design and the use of recycled materials. The aim is to promote collaboration between different sectors and the application of policies and programs that promote circularity throughout the value chain, from production to waste management. The benefits of this economy are notable both environmentally and economically, as it contributes to reducing dependence on natural resources, minimizing waste generation and stimulating innovation, which can have a positive impact in the fight against climate change. the conservation of biodiversity and the generation of employment. In summary, the circular economy implies a paradigm transformation towards a system that is more efficient, durable and sustainable, with the aim of harmonizing human needs with the preservation of the environment.
La economía circular se presenta como un enfoque innovador que busca revolucionar la manera en que producimos, consumimos y gestionamos los recursos, la implementación de políticas y programas de economía circular es esencial para lograr un desarrollo sostenible. Esto implica adoptar prácticas preventivas, fomentar la reutilización, el reciclaje, promover el ecodiseño y el consumo responsable. Dentro de este marco, el diseño de productos y materiales se orienta a mantener su valor y utilidad durante el mayor tiempo posible, mediante prácticas como el diseño sostenible, y la utilización de materiales reciclados. Se busca fomentar la colaboración entre distintos sectores y la aplicación de políticas y programas que impulsen la circularidad en toda la cadena de valor, desde la producción hasta la gestión de residuos. Los beneficios de esta economía son notables tanto a nivel ambiental como económico, ya que contribuye a reducir la dependencia de recursos naturales, minimizar la generación de residuos y estimular la innovación, lo que puede tener un impacto positivo en la lucha contra el cambio climático, la conservación de la biodiversidad y la generación de empleo. En síntesis, la economía circular implica una transformación de paradigma hacia un sistema que es más eficiente, duradero y sostenible, con el objetivo de armonizar las necesidades humanas con la preservación del medio ambiente.
Keywords: ECONOMIA CIRCULAR; SOSTENIBILIDAD; REUTILIZACION; RECICLAJE